2015
DOI: 10.1016/j.bbr.2014.02.052
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Involvement of insulin-like growth factor-1 in chemotherapy-related cognitive impairment

Abstract: Here we examined the involvement of insulin-like growth factor 1 (IGF-1) on chemotherapy-induced cognitive impairment. Sixty-four ovariectomized female Sprague-Dawley rats were included in the study and given cyclophosphamide, methothrexate, and 5-Fluorouracil (CMF) drug combination or saline (control). CMF was given once a week for 4 weeks. In one experiment, behavioral testing using the cued learning and spontaneous object recognition tasks were performed either: at the end of treatment or 4 weeks after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…We found that the Akt and ERK1/2 pathways were involved in doxorubicin and cyclophosphamide induced cognitive changes and need to be further studied. Our finding that both ERK1/2 and Akt pathways are activated are similar to those recently of Briones et al [32], however, these investigators did not use intact female rats in their study as a comparison.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the Akt and ERK1/2 pathways were involved in doxorubicin and cyclophosphamide induced cognitive changes and need to be further studied. Our finding that both ERK1/2 and Akt pathways are activated are similar to those recently of Briones et al [32], however, these investigators did not use intact female rats in their study as a comparison.…”
Section: Discussionsupporting
confidence: 91%
“…Unraveling the precise mechanisms underlying CRCI may facilitate the identification of novel pharmacologic treatment strategies. Several animal studies focusing on the impact of chemotherapy on cognition have suggested promising interventions, such as preventing oxidative stress associated with chemotherapy using 2‐Mercaptoethane sulfonate, N‐acetylcysteine, or melatonin; stimulating neurogenesis with insulin‐like growth factor‐1, fluoxetine, or glucose; and treatments with glutamate receptor antagonists, such as dextromethorphan or memantine, that ameliorate chemotherapy‐induced CRCI. The arrival of new targeted agents and immunotherapies that may influence cognition, either alone or in combination with traditional anticancer agents, will necessitate further preclinical work to understand and potentially improve adverse side effects on cognition.…”
Section: Interventionmentioning
confidence: 99%
“…At the same time, antiinflammatory cytokines, such as Interleukin-1 receptor antagonist (IL-1RA) and Interleukin-10 (IL-10) are decreased [ 30 ]. Hypothesized mechanisms of CRCI also include decreased levels of neurotrophic and growth factors, such as brain-derived neurotrophic factor (BDNF), insulin-like growth factor 1 (IGF-1) and vascular endothelial growth factor (VEGF) [ 31 35 ].…”
Section: Introductionmentioning
confidence: 99%